Tornare a vivere a causa dell’altro. Seneca, l’epistola 104 e l’amore coniugale - Torre, Chiara (Lucius Annaeus Seneca, 2022)
At the beginning of Letter 104 Seneca claims to be especially careful of his own eldness because of his concern for his young wife Paulina, and as it were return to life for her sake. Until what point such this attitude is consistent with the cornerstone dogma of the autarcheia of the wiseman? Therefore, facing the issue of the social and relational affective responses in the Stoic Theory of emotions, could Letter 104 allow us to find out some fresh argument? Trying to answer these questions is a challenging task, which could also highlight the issue about the relationship between the emotions of the sapiens and those of proficiens, as it is especially dealt with in Letter 104 by the mean of the intertextuality, namely some echoes of Ovid and Vergil.